Мистецький синтез у шахосонеті - Мойсієнко, А. (Слово і Час, 2021)
Стаття присвячена одному з візуальних видів синкретичної поетичної творчості — шахопоезії. На матеріалі збірок В. Капусти «Картатий материк» та «Негарантована мігрантіана» проаналізовано
шахосонетний доробок поета, який уписав нову сторінку в українську
візуалістику, запропонувавши рівноправне поєднання чітко структурованої літературної форми із шаховою задачею. Звернено увагу
на трансформаційні особливості сонетного рядка, що прочитується
паліндромно-панторимно. Панторима служить версифікаційною і
композиційною основою шахового вінка сонетів «Рокірування. Зір гербарій», який аналізується з урахуванням транспозиційності тих чи
тих характеристик на шахово-композиційне підґрунтя. The article focuses on one of the visual types of syncretic poetry — chess poems. Years ago
Anatolii Moisiіenko initiated the chess poetry genre in Ukrainian literature; in a number
of critical papers, he presented the specifics of construction and functioning of such artistic
structures, which are basically characterized by the symbiosis of proper poetry and chess
composition. In this article, the author uses Viktor Kapusta’s books of poems “The Checkered
Continent” and “Unguaranteed Migrations” to analyze the chess sonnets of the poet
who added a new page to the history of Ukrainian visual literary art by proposing a peerto-
peer combination of a strictly structured literary form and a chess problem. The aim is to
conceptualize the figurative and compositional relations within the sonnet structure itself,
which relies on the artistic palette of the chess game, with its diversity of geometric abstractions,
local mise-en-scènes of unpredictable theatrical performances played out on the chessboard
by wooden pieces — or on the chessboard of readers’ imagination. Attention is drawn
to the transformational peculiarities of the sonnet line, read in a palindromic and pantorhymic
way. The pantorhyme is the versificational and compositional basis for the chess
sonnet sequence “Castling. A Herbarium of Stars”, which is analyzed here with regard to
the transposition of some characteristics to the realm of chess composition. A diagrammed
chess problem becomes a specific chess component of a sonnet sequence, where, for example,
the variants of the solution (Black’s defensive moves and White’s attacking responses)
correspond to the poetic lines making up the fourteen sonnets whereas the problem’s threat,
like a principal poem, concentrates all the mentioned chess movements in a single variant.